Determination of glutathione and glutathione disulfide in human whole blood using HPLC with coulometric detection: A comparison with fluorescence detection - Kanďár, Roman; Žáková, Pavla; Marková, Miroslava; Lotková, Halka; Kučera, Otto; Červinková, Zuzana (Collection of Czechoslovak Chemical Communications, 2011)
We describe a relatively simple method for the determination of glutathione (GSH) and glutathione disulfide (GSSG) in human whole blood. We have used an HPLC with coulometric electrochemical detection for the simultaneous measurement of GSH and GSSG. Diluted and filtered trichloroacetic acid extracts were injected directly into the HPLC system and were eluted isocratically on a Polaris 5u C18-A, 250 × 4.6 mm analytical column. Glutathione in samples extracted with trichloroacetic acid and diluted with 1.0 mM hydrochloric acid was stable at 4 °C for at least 8 h. The analytical performance of this method is satisfactory: the intra-assay and inter-assay coefficients of variation were below 10%. Quantitative recoveries from spiked whole blood samples were at intervals 91.6–97.6% for GSH and 85.0–104.4% for GSSG. The linear range is 5.0–2000.0 µmol/l, with a detection limit of 2.1 µmol/l (signal-to-noise ratio = 3) for GSH and 2.0–250.0 µmol/l, with a detection limit of 0.9 µmol/l for GSSG.
Keywords: Fluorescence Polarization Immunoassay; fluorescenční polarizační imunologické testy; glutathiondisulfid; elektrochemické techniky; Blood; Fluorometry; krev; Glutathione Disulfide; fluorometrie; Electrochemical Techniques